منهج الشيخ بكر أبو زيد حول فكرة "وحدة الأديان" من خلال كتابه "الإبطال لنظرية الخلط بين دين الإسلام وغيره من الأديان" : دراسة تحليلية - بلوي، موسى بن عبدالله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This study aims at examining the characteristics and features of Sheikh Baker's methodology in unraveling the idea of “unification of all religions” through his book entitled “Nullifying the Theory of Mixing Islam with other Religions”. To explore this aim، this study employed two methodologies; analytical and inductive. The thesis consists of four chapters and a conclusion. The first chapter contains an introduction to the study while the second chapter focuses on the biography of the Sheikh with his great books. The third chapter explores the perspective of sheikh Baker in understanding the notion of “unification of all religions” while citing some of the contemporary images and signs attributed to this theory/notion. The last chapter focuses on the major features of the Sheikh's methodology in dealing with the theory of “unification of all religions”. However، I have concluded by stating some results related to the thesis topic، among which is the interest of the Sheikh in discussing similar ideologies like this، with his explanation of the contradictions related to the underlying theory. More so، he states the reason why Muslims should have certain knowledge about the reality of Islam as a religion which has abrogated previous religions، and has come to stay till the Day of Judgment. Furthermore، this theory is one of the modern terms that question reality with goals left unanswered. The images and signs related to it are just mere illusive efforts and unrealistic persistence in the bid to disseminate it to the people. Lastly، this theory، however، is susceptible in making the Muslims mislay the significance of Islam due to the fact that it is being compared with other religions and ultimately mixing truth with falsehood.